Context Matters: Concepts of School Engagement in the Context of Geographic Isolation - Gary Andersen; Linda E Feldstein (The Advocate, 2020)
This case study research represents an attempt to gain a better understanding of conceptions of school engagement in a rural, isolated, agricultural mid-western community. Local school administrators, in collaboration with a regional university, chose to make student engagement the focus of deep inquiry in order to better address student concerns, improve teaching, and student outcomes (Association of Teacher Educators, 2007). Researchers interviewed students, teachers, and parents in a local high school, using an interview protocol specifically designed for each constituency. The study results point to a mostly behavioral, or compliance driven concept of engagement among all groups interviewed, but further examination of data also show that students tended to voice a desire for a higher degree of agentic engagement, along with a strong need for positive relationships with teaching faculty. This points to a need for teacher educators to more deeply address preservice students’ understanding of engagement, as well as a potential to shift to a conceptual understanding of student engagement that is more agentic in nature. Implications include avenues toward broadening conceptions of engagement among staff, students, and parents; increased understanding and implementation of educational strategies designed to increase engagement at both the classroom and school levels; and catalyzing changes in educator preparation programs that improve candidates’ understanding of and ability to be effective in isolated rural school communities.
Keywords: Student engagement; rural education; school redesign; KSDE redesign